The impact of wrong‐site surgery on dental undergraduate teaching: a survey of UK dental schools. (23rd December 2020) - Dargue, Anna; Fyfe, Eithne; French, Kathryn; Ali, Kamran; Bailey, Edmund; Bell, Aileen; Bolt, Robert; Bulsara, Yogesh; Carey, James; Emanuel, Charlotte; Green, Rachel; Khawaja, Nadine; et al.
ABSTRACT: Introduction: Patient safety within dental education is paramount. Wrong‐site surgery (WSS) tooth extraction is not uncommon and is a significant never event (NE) in dentistry. This study aimed to explore dental schools' undergraduate experience of NEs, safety interventions implemented and the impact on student experience. Methods: All 16 UK dental schools were surveyed via email. Results: The response rate was 100%. A modified World Health Organization (WHO) checklist was used within institutions (94%) including pre‐operative briefings and recording teeth on whiteboards (81%, respectively). Students were directly supervised performing extractions (63%) utilising a 1:4 staff: student ratio. WSS by students was reported in 69% of schools, with student experience being impacted by an increased patient safety focus. Discussion: This study demonstrated an increased utilisation of an adapted WHO checklist. Modification of practices to ensure patient safety was demonstrated at all schools, irrespective of student WSS occurrences. Institutions experiencing student NEs commonly implemented WHO checklists and recording teeth for extraction on whiteboards. Other strategies included direct staff supervision and pre‐operative briefings. Conclusion: UK dental schools have increased the emphasis on patient safety by the implementation of national healthcare models, for example WHO checklists and pre‐operative briefings. These strategies both aim to improve communication and teamwork. Increased levels of staff supervision foster greater quality of teaching; however, this has resulted in reduced student clinical experience. A proposed minimum standard for undergraduate surgery is suggested to ensure safe and competent dental practitioners of the future.